ANALISIS LITERASI MATEMATIS SISWA MTS SUNAN AMPEL DALAM MENYELESAIKAN SOAL PISA DITINJAU DARI GAYA KOGNITIF - MAYANG SARI; Anisatul (Universitas Nahdlatul Ulama Pasuruan, 2023)
The demands of students' abilities in mathematics are not just having the ability to count, but being able to use it in solving everyday problems. This study aims to analyze the mathematical literacy abilities of class IX students of MTs Sunan Ampel in solving PISA questions in terms of cognitive style. The research method used is descriptive qualitative. The selection of subjects in this study began with giving the GEFT test to determine students' cognitive styles included in the category of field independent (FI) or field dependent (FD), then one student from each cognitive style was taken to be given a literacy test using PISA questions. The research instruments used in this research include mathematical literacy ability tests, cognitive style tests, and interviews. Previously, the three instruments were validated first by several experts to determine the suitability of the three instruments. Data analysis techniques in this research include data reduction, data presentation, and drawing conclusions.The results of this research show that students with a field independent (FI) cognitive style tend to be superior to students with a field dependent (FD) cognitive style. Because field independent (FI) students have fulfilled three literacy indicators, namely the indicators of formulating, using and interpreting. Meanwhile, field dependent (FD) students have only met two indicators, namely formulating and using, but have not yet met the interpreting indicator.Keywords: Student difficulties, math word problems, statistics, students' math abilities.